The impact of benchmarking approach towards performance in construction industry - Umairah ‘Aqilah, Sudin (2015)
The benchmarking approach is important for each industry, mostly industry that used this tool is construction, hotel management, and food and beverage industry. This study is to identify the factor of benchmarking that influence performance improvement in construction industry and to rank the impact of using benchmarking tool for construction industry. Both of the objectives have huge influence to ensure a success of the project. Therefore, factor of benchmarking also give an impact towards performance of the company. Unimportant factor that used when benchmarking an industry will bring nothing benefits for the organization. The population of this study is 75 employees from executive positions that work in construction companies at Kuantan, Pahang Darul Makmur. The sample size is use as the units of analysis, 63 employees which were from executive position was selected. In conducting this study, random sampling survey method was being used and this questionnaires survey was distributed to respondent by email (Google doc). For data analyzing, this data was carried out by using Descriptive statistic is drawn from Statistical Package Social Science (SPSS) outputs. The finding from this study indicate that the factor of benchmarking have an impact towards performance in construction industry whether improve or become worst.